Review of 3D printed electronics : metallic nanoparticles inks - Tan, Hong Wei (2018)
There are growing interests among researchers to use additive manufacturing technologies for on-demand fabrication of functional electronic components and circuitries. The conductive ink is one of the most important components in 3D printed electronics, in which the material properties of the ink determine the mechanical and electrical properties of the printed patterns. Therefore, there is great importance to look into and understand the different types of ink used in 3D printed electronics. In this review paper, we discuss the overview of the metallic nanoparticles inks used for 3D printed electronics.